Linking scores on the 4- and 5-item versions of the Satisfaction with Life Scale in people with traumatic brain, spinal cord, or burn injury: a National Institute on Disability, Independent Living, and Rehabilitation Research Model System study - Alyssa M. Bamer; Kara McMullen; Anne Deutsch; Mitch Sevigny; Tracy Mroz; Shelly A. Wiechman; Jeffrey C. Schneider; Dagmar Amtmann (SpringerOpen, 2021)
Abstract Background The Satisfaction with Life Scale (SWLS) is a widely used measure of subjective well-being. Recent evidence indicates the fifth item of the scale reduces the reliability of the scale and is inappropriate for use in traumatic injury populations. The purpose of this study was to develop a linking procedure between the five-item version of the SWLS and a modified four-item version, which removes the problematic item, for use in Spinal Cord (SCI), Traumatic Brain (TBI), and Burn Injury populations. Methods Proration (i.e. adding the mean of the four items to their total) was identified as a potential linking solution that could be easily implemented in clinical or research settings. The validity of the proration approach was evaluated by examining mean differences, cross group classification by SWLS category, score correlations, the intraclass correlation coefficient, and visual inspection of Bland-Altman plots in a large sample of SCI, TBI, and Burn Injury survivors who were participants in the National Institute on Disability, Independent Living, and Rehabilitation Research (NIDILRR) Model Systems' National Databases. Results A total of 17,897 (SCI n = 8566, TBI n = 7941, and Burn n = 1390) participants were included in this study. SWLS scores ranged from 5 to 35, and the average score difference between directly derived and prorated scores was 0.39 points. A large majority of the sample (93%) had score differences of < 4 points (i.e. approximately 0.5 SD). The correlation between the prorated and directly derived scores was very high (r = 0.97) and the ICC value indicated excellent reliability (ICC = 0.97). Conclusions This study provides a valid scoring approach for researchers or clinicians who don't want to lose continuity with previously collected data but prefer to switch to the modified four-item version of the SWLS. Clear guidance is provided for traumatic injury researchers or clinicians on how to implement the proration scoring approach.